PENGARUH DOSIS PUPUK NPK DAN NAUNGAN TERHADAP PERTUMBUHAN SEMAI JABON MERAH (Anthocephallus macrophyllus Havil) SAMPAI UMUR 4 BULAN - , GANDHES WENING TYAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fertilization on seedling red jabon (Anthocephallus macrophyllus Havil) is needed to accelerate growth and improve the quality and seed quality red jabon. Seedling quality and quality can be seen from the high growth of seedlings, stem diameter and number of leaves were large lot. This study was conducted to determine the effect of NPK fertilizer and shading on the growth red high jabon (Anthocephallus macrophyllus Havil). The research was conducted at the Center for Biotechnology and Forest Tree Improvement (BBPBPTH), in Purwobinangun,Pakem, Sleman, Yogyakarta, for approximately 2 month. The study design used Completely Randomized Design (CRD) with treatments as follows: 1. Main plots in this study is the shade factor that is (1) open and (2) shaded 50%